Tipologi Loyalitas dan Kepuasan Nasabah Dalam Mengoptimalkan Customer Relationship Management (CRM) di BPRS SPM Pamekasan - Sudianto Sudianto; Saiful Umam (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
The importance of customer loyalty and satisfaction positively impacts the growth of Sharia banks. Loyalty and satisfaction from a customer will be created if a harmonious relationship exists between the two parties, namely the customer and the Sharia bank, otherwise, a disharmonious relationship will damage the cooperation between the two. So it does not rule out the possibility that Islamic banks will experience problems. This research aims to determine CRM implementation and customer loyalty and satisfaction factors at BPRS SPM Pamekasan. This type of research uses descriptive qualitative methods. The results of this research show that the implementation of Customer Relationship Management implemented by BPRS SPM Pamekasan includes: Being able to identify customer desires, obtain new customers, retain old customers, convince customers to continue using BPRS SPM products and services, and provide good after-sales service. To create success in the Customer Relationship Management strategy which can generate loyalty and satisfaction for BPRS SPM customers, this is by improving the quality of service provided to customers, with the aim of good service, a good relationship will also be built between BPRS SPM and customers thereby creating loyal customers. and feel satisfied.